The Shapes of Early English Poetry : Style, Form, History - Weiskott, Eric; Dumitrescu, Irina (Book collections on Project MUSE., 2019)
This volume contributes to the study of early English poetics. In these essays, several related approaches and fields of study radiate outward from poetics, including stylistics, literary history, word studies, gender studies, metrics, and textual criticism. By combining and redirecting these traditional scholarly methods, as well as exploring newer ones such as object-oriented ontology and sound studies, these essays demonstrate how poetry responds to its intellectual, literary, and material contexts. The contributors propose to connect the small (syllables, words, and phrases) to the large (histories, emotions, faiths, secrets). In doing so, they attempt to work magic on the texts they consider: turning an ordinary word into something strange and new, or demonstrating texture, difference, and horizontality where previous eyes had perceived only smoothness, sameness, and verticality.